Scheming in syntax: analysing scammer-victim conversations in Malaysian e-commerce scams - Nursyaidatul Kamar Md Shah,; Ameiruel Azwan Ab Aziz,; Amirah Mohd Juned,; Ariff Imran Anuar Yatim,; Wan Farah Wani Wan Fakhruddin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The e-commerce scam cases reported worldwide are highly alarming, with enormous financial losses. The empirical investigation of this research focuses on the linguistic strategies utilised by scammers as their modus operandi in duping their targets. This research aims to analyse the common linguistic features of scammers and identify the steps, strategies, and patterns prevalent in e-commerce scams in Malaysia by conducting a thorough linguistic analysis of real conversation exchanges between scammers and victims. This qualitative study compiled and established a database of e-commerce scam cases from social media. From this database, 14 sets of online communications between scammers and 14 Malaysian victims were chosen and examined using the content analysis method—one facet of the data analysis involved studying scammers' linguistic styles and patterns in persuading their targets. The analysis revealed various persuasive linguistic tactics employed by the scammers to deceive the victim, which are friendly expressions, urgent disclosure, manipulated statements, persuasive language, leveraging authority declarations, fabricated social references and appealing offers. Guided by speech act theory, this study shows that scammers use locutionary acts (specific words and phrases) to appear legitimate, illocutionary acts (intentions behind the words) to make false promises or issue threats, and perlocutionary acts (impact on the victim) to evoke trust, fear, or greed. This study demonstrates how scammers use subtle yet effective language to deceive individuals out of money. Contrary to the common perception of the gullible or vulnerable person "falling for" a scam, the findings reinforce how scammers are effective language manipulators who employ strategies to reassure victims and disassemble any reason for concern. The study highlights the importance of being vigilant to these tactics and implementing caution when engaging with unfamiliar online sellers. It emphasises the need to verify sellers' legitimacy and be wary of any requests for payment before receiving the purchased item.